Women's health in focus: contemporary challenges, therapeutic solutions and historical perspectives - A. D. Makatsariya; A. V. Vorobev (Акушерство, гинекология и репродукция, 2025)
This journal issue presents studies devoted to actual questions of women's health, including thrombophilia impact on pregnancy, determination of biological age in the reproductive period, and the relationship between placental pathology and thrombophilic disorders. Innovative approaches to diagnostics and treatment are considered, such as plasmapheresis in antiphospholipid syndrome, organ-preserving strategies in placenta accreta spectrum, and prospects for passive fetal monitoring using machine learning. Immune-mediated thrombotic complications, including vaccine-induced thrombotic and heparin-induced thrombocytopenia, are highlighted. Clinical cases of rare pathologies are presented, such as lipodermatosclerosis in pregnant women, complete androgen insensitivity syndrome, and laparoscopic cerclage for cervical insufficiency. The final material is dedicated to Robert Edwards historical role in the development of in vitro fertilization.